The impact of the COVID-19 pandemic on endurance and ultra-endurance running - Scheer, V.; Valero, D.; Villiger, E.; Rosemann, T.; Knechtle, B. (Medicina, 2021)
Background and objectives: The COVID-19 outbreak has become a major health and economic crisis. The World Health Organization declared it a pandemic in March 2020, and many sporting events were canceled. Materials and Methods: We examined the effects of the COVID-19 pandemic on endurance and ultra-endurance running (UER) and analyzed finishes and events during the COVID-19 pandemic (observation period March 2020-October 2020) to the same time period preCOVID-19 outbreak (March 2219-October 2019). Results: Endurance finishes decreased during the pandemic (459,029 to 42,656 (male: 277,493 to 25,582; female 181,536 to 17,074; all p < 0.001). Similarly, the numbers of endurance events decreased (213 vs. 61 events; p < 0.001). Average marathon finishing times decreased during the pandemic in men (5:18:03 ± 0:16:34 vs. 4:43:08 ± 0:25:08 h:min:s (p = 0.006)) and women (5:39:32 ± 0:19:29 vs. 5:14:29 ± 0:26:36 h:min:s (p = 0.02)). In UER, finishes decreased significantly (580,289 to 110,055; p < 0.001) as did events (5839 to 1791; p < 0.001). Popular event locations in United States, France, UK, and Germany decreased significantly (p < 0.05). All distance and time-limited UER events saw significant decreases (p < 0.05). Conclusions: The COVID-19 pandemic has had a significant effect on endurance and UER, and it is unlikely that running activities return to pre-pandemic levels any time soon. Mitigation strategies and safety protocols should be established.